PENGUKURAN KUALITAS SISTEM INFORMASI AKADEMIK IGRACIAS MENGGUNAKAN METODE WEBQUAL 4.0 DAN IPA - Eben Haezer Siregar; Dwi Januarita; Citra Wiguna (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2021)
Academic information system has an important role for an educational institution, in addition to providing academic services, its presence can increase the advantage to compete with other universities. IT Telkom Purwokerto has an academic information system, namely igracias which is used for student academic purposes. The development of the igracias information system needs to be done to improve the quality of the IT Telkom Purwokerto igracias information system. This study uses the Webqual 4.0 method which consists of 3 variables, namely usability, information quality, service interaction quality and Importance Performance Analysis as well as data collection using a questionnaire that results in the calculation of the gap value with the highest average being -0.37 on the service interaction quality and service interaction quality variables. The lowest average gap value is -0.35 on the information quality variable and the overall conformity average value is 0.905. Based on the results of these calculations indicate that the quality of the igracias information system is still not appropriate or meets user expectations so that improvements and developments are needed by the management. Keywords: Quality Analysis, WebQual 4.0, Importance Performance Analysis